1995
DOI: 10.1507/endocrj.42.413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cabergoline, a Dopamine Agonist, on Estrogen-Induced Rat Pituitary Tumors: In Vitro Culture Studies.

Abstract: Abstract.Cabergoline (CG) is a dopamine agonist that inhibits secretion of prolactin (PRL) and growth hormone.The purpose of this study was to investigate the PRL-lowering effect and antitumor effect of cc on estradiol-induced rat pituitary tumors in vitro and to elucidate these mechanisms. We compared the effects of CG with those of bromocriptine (BC) in terms of the inhibition of hormone secretion as well as antitumor effects on rat pituitary tumors. Primary cultures of dissociated pituitary tumor cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 39 publications
1
11
0
1
Order By: Relevance
“…This drug suppresses PRL release in in vitro and in vivo rodent models [11], [12], and decreases cell viability in non-functioning human pituitary adenomas [36]. We previously reported that CAB induces apoptosis of lactotropes only when cells are cultured in the presence of E2 [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This drug suppresses PRL release in in vitro and in vivo rodent models [11], [12], and decreases cell viability in non-functioning human pituitary adenomas [36]. We previously reported that CAB induces apoptosis of lactotropes only when cells are cultured in the presence of E2 [2].…”
Section: Discussionmentioning
confidence: 99%
“…Cabergoline (CAB), a D2R agonist, is the most effective compound for pharmacological treatment of prolactinomas [10], strongly reducing PRL secretion and lactotrope proliferation [11], [12]. Although DA agonists have been proven to be successful in normalizing serum PRL levels, a subset of patients with prolactinomas does not respond to CAB, suggesting that D2R expression is altered.…”
Section: Introductionmentioning
confidence: 99%
“…Cabergoline 7.1 Therapeutic profile CAB strongly suppresses PRL secretion both in vivo and in vitro. A significant inhibition of PRL secretion was observed within 12 h after treatment with CAB and BRC in cultured pituitary cells from oestradiol-induced rat pituitary tumours [63,64]. The effect of CAB and BRC was antagonised by sulpiride or haloperidol and PRL secretion and inhibition of de novo synthesis was more pronounced with CAB than BRC treatment [64].…”
Section: Othersmentioning
confidence: 96%
“…A significant inhibition of PRL secretion was observed within 12 h after treatment with CAB and BRC in cultured pituitary cells from oestradiol-induced rat pituitary tumours [63,64]. The effect of CAB and BRC was antagonised by sulpiride or haloperidol and PRL secretion and inhibition of de novo synthesis was more pronounced with CAB than BRC treatment [64]. In various animal models, CAB markedly reduced plasma PRL levels in vivo after single or multiple doses and the PRL-lowering effects appeared 2 -8 h after administration lasting for ≥ 72 h [65,66].…”
Section: Othersmentioning
confidence: 98%
“…Cabergoline, a selective D2 agonist, strongly suppresses PRL secretion and synthesis (9). A remarkable tumor-shrinking effect has been recognized in patients with not only microprolactinomas but also macroprolactinomas (10).…”
Section: Discussionmentioning
confidence: 99%